(untitled) (Bangladesh Critical Care Journal, 2022)
Background: Bell’s palsy is the most common cause of lower motor neuron type facial nerve palsy and one of the most frequently encountered presentations in Department of Neurology. Initial treatment involves oral corticosteroids, possible antiviral drugs, protection of the eye from desiccation and physiotherapy. But in case of patients with Bell’s palsy and diabetes mellitus (DM) decision of prescribing steroid is a major concern due to risk of hyperglycaemia and still a point of conflict. Aim of this study is to observe the outcome of diabetic patients with Bell’s palsy with and without steroid therapy. Methods: This retrospective study was conducted from January 2017 to December 2020, in Department of Neurology of BIRDEM General Hospital, Shahbag, Dhaka, Bangladesh. During this period 50 adult diabetic patients with Bell’s palsy were recruited retrospectively from hospital records according to inclusion criteria and divided into two groups depending upon the duration of symptoms and prescribing steroid. Group I consisted of patients with Bell’s palsy who attended after 72 hours of onset of symptoms and was not prescribed steroid or antiviral drugs, whereas Group II included patients attending within 72 hours of onset of symptoms and received steroid and antiviral drugs. House-Brackmann (H-B) Grading system was used to assess the severity of facial dysfunction. Patients of Grade III and above were recruited in this study and during follow up Grade I and II were considered as recovered. All participants of Group II received prednisolone in divided doses of up to 60 mg for 5 days and then tapered over next 5 days along with the antiviral agents. Patients in the Group I were given supportive care. All patients of both the groups received physiotherapy for facial asymmetry and medication for eye care along with close monitoring and management of diabetes and other comorbidities. H-B Grades at onset, after 10 days, at the end of 1st and at 3rd month after facial paralysis were assessed. Recovery time and the number of patients who demonstrated improvement were compared between the groups. Results: Total 50 adult diabetic patients with Bell’s palsy were included. Mean age at presentation was 48.5 ± 13.6 years, 44% were male and 56% female. Hypertension (HTN) was present in 50% cases. A total of 30 patients (60%) received oral steroid with anti-viral drugs and 20 (40%) received only supportive treatment. Significant statistical difference was observed with regard to H-B Grades, recovery time and number of patients between steroid group (Group II) in comparison to patients of non-steroid group (Group I) after 10 days (p 0.007), at 1st month ( p <0.001) and at 3rd months (p <0.001) after facial paralysis. Among comorbidities HTN (p 0.021), Glycated haemoglobin (HbA1c) (p 0.033) and High density lipoprotein (HDL) (p 0.005) contributed to the outcome. Conclusion: From the present study it is observed that patients with DM with Bell’s palsy, the recovery of facial functions may be satisfactory with steroid therapy. Bangladesh Crit Care J March 2022; 10 (1): 33-37